A critical concentration of N-terminal pyroglutamylated amyloid beta drives the misfolding of Ab1-42 into more toxic aggregates. (October 2016) - Galante, Denise; Ruggeri, Francesco Simone; Dietler, Giovanni; Pellistri, Francesca; Gatta, Elena; Corsaro, Alessandro; Florio, Tullio; Perico, Angelo; D'Arrigo, Cristina
Abstract: A wide consensus based on robust experimental evidence indicates pyroglutamylated amyloid-β isoform (AβpE3-42) as one of the most neurotoxic peptides involved in the onset of Alzheimer's disease. Furthermore, AβpE3-42 co-oligomerized with excess of Aβ1-42, produces oligomers and aggregates that are structurally distinct and far more cytotoxic than those made from Aβ1-42 alone. Here, we investigate quantitatively the influence of AβpE3-42 on biophysical properties and biological activity of Aβ1-42. We tested different ratios of AβpE3-42/Aβ1-42 mixtures finding a correlation between the biological activity and the structural conformation and morphology of the analyzed mixtures. We find that a mixture containing 5% AβpE3-42, induces the highest disruption of intracellular calcium homeostasis and the highest neuronal toxicity. These data correlate to an high content of relaxed antiparallel β-sheet structure and the coexistence of a population of big spheroidal aggregates together with short fibrils. Our experiments provide also evidence that AβpE3-42 causes template-induced misfolding of Aβ1-42 at ratios below 33%. This means that there exists a critical concentration required to have seeding on Aβ1-42 aggregation, above this threshold, the seed effect is not possible anymore and AβpE3-42 controls the total aggregation kinetics.